Short Paper: Bus-based Packetized Scan Architecture Trade-offs for Heterogeneous Multi-Core SoCs - Iwata, Hiroyuki; AbdAlwahab, Mahmoud; Press, Ron; Sugiura, Ohki (Proceedings - International Test Conference, 2024)
Choosing a DfT architecture for heterogeneous multi-core SoCs is constrained by various business, design and industrial-test requirements. SSN is a bus-based packetized data distribution scan architecture designed to address these requirements. A comparison between SSN and previous hierarchical DfT approaches is shown. A specific project SoC requirements is reviewed with packetized scan delivery architecture trade-offs. Results show 2X scan data transfer rate while adhering to pinning, area and physical design constraints.